STRATEGI PENGAWASAN LEMBAGA PEMERINTAH DI KOTA BANDA ACEH BERBASIS PREVENTION CONTROLLING HYBRID SYSTEM - Dewi, Yunita (Yayasan Panca Bakti Wiyata Pangandaran, 2024)
The strategy of government institution supervision based on prevention controlling hybrid system is an innovative approach that aims to improve the effectiveness and efficiency in public administration supervision. In today's digital era, the challenges faced by government institutions are increasingly complex, including limited human resources, inadequate technological infrastructure, and the need for transparency and accountability. This study identifies various problems that hinder the implementation of an effective supervision system, such as resistance to change and challenges in system integration. Through a hybrid approach that combines traditional supervision methods and information technology, this strategy is expected to create a more responsive and adaptive supervision environment. The results of this study indicate that increasing human resource capacity, developing technological infrastructure, and implementing better transparency and accountability principles are the keys to achieving optimal supervision goals. Thus, this strategy not only contributes to improving the performance of government institutions, but also to increasing public trust in public institutions.